ANALISIS PRAKTIK PERATAAN LABA PADA INDUSTRI REAL ESTATE DAN PROPERTI YANG BEREPUTASI BAlK DI BURSA EFEK INDONESIA - Wijaya, Mulyawati (Widya Mandala Surabaya Catholic University, 2009)
Income smoothing is a manager's deliberate effort in choosing accounting method to normalize income in order to reach a stable income. Eckel index showed 9 corporate with good reputation and 6 corporate with bad repultation doing income smoothing practice. Independent Sample T-Test showed that there is a different income smoothing index between corporate with good and bad reputation. From t test, financial leverage variable in real estate and property industry with good reputation injluenced income smoothing index. F test showed that size, profitability, financial leverage, and operating leverage variable in real estate and property industry with good reputation simultaneously injhlenced income smoothing index.